EKSISTENSI KARYA KARTUNIS MEDIA CETAK DI ERA KONVERGENSI MEDIA: EKSISTENSI KARYA KARTUNIS MEDIA CETAK DI ERA KONVERGENSI MEDIA - Supradaka, Supradaka (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
AbstractIn Indonesia cartoon dynamic having relevance with that of printing media in thecountry. By the languid of printing media industry, newspaper and magazine specially, ithad resulted in cartoonists who have energy to be freelance contributor at mediaprinting, currently, they had become anxious and apprehensive because cartooncolumns/rubrics had been provided for them by business considerations one by one hadbeen ready minimized and reduced by such media in media convergence era. However,the objective of this research is to know cartoonist work existence in printing media as wellas tactic and strategy of cartoonists in order to stay exist in media convergence era. Thisresearch uses descriptive-qualitative method by technique of primary data collectionobtained by participant and interview observation. Regarding secondary data it isobtained by library study. Conclusion from this research is that to maintain work existencein media convergence era, cartoonists should increase science from multiple knowledgedisciplines, creative process while accentuating group work model. Scheduled cartoonexhibition, skill increasing and digital technological mastering.